The provisions of the tsar`s ukase of 27 October 1864 on the maintenance and management of monasteries in the Kingdom of Poland - KANTOR, ROBERT (Prawo Kanoniczne, 2018)
Times in the 19th century, the partitioning powers effectively limited the functioning of the Catholic Church on Polish lands, including the functioning of orders and monasteries that were subject to them. After the fall of the January Uprising, the Russian authorities took repressive measures on the territory of the Kingdom of Poland by dissolving most of monasteries existing at that time. However, the dissolution of monasteries resulting from the tsar`s ukase of 27 October (8 November according to the Gregorian calendar) 1864 was of major significance for the functioning of orders in the Kingdom of Poland. As a consequence, 115 monasteries were dissolved which became considered “closed” or “dissolved” (fewer than 8 monks or nuns in a monastery). Out of 155 male monasteries and 45 female monasteries, 20 male ones and 7 female ones were left, which, as self-funded but without the right to accept novices (called self-funded monasteries), could function until the number of their members dropped down to 7 people. The subject matter hereof is the presentation of legal rules contained in the Ukase of 27 October (8 November) 1864, relating to the dissolution of monasteries in the Kingdom of Poland. Therefore, the only source used herein shall be the content of the Ukase and “Rules and regulations on the maintenance and management of Roman Catholic monasteries in the Kingdom of Poland of 22 November (4 December) 1864”. In the existing literature on the history of law, there are no references to the legal analysis of rules contained in the Ukase.